THE ROLE OF SOCIAL MEDIA AND LIFESTYLE TRENDS IN INFLUENCING THE SAVING HABITS OF YOUNG PEOPLE IN YOGYAKARTA - Oxi Alvira Jasmine; Nurfauziah (Finance : International Journal of Management Finance, 2025)
The development of technology and social media has brought significant changes to the lifestyle of young people, especially in Yogyakarta, which is known as an educational city with widespread internet access. This study aims to analyze the role of social media and lifestyle trends in influencing the saving habits of young people in Yogyakarta. The research method used is a quantitative approach with data collected through surveys of 120 young social media users in Yogyakarta. The sampling technique employed non probability sampling using a purposive sampling method. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The results show that social media and lifestyle trends have a positive effect on the consumptive behavior of young people. Furthermore, consumptive behavior has a negative effect on saving habits. In addition, consumptive behavior also negatively mediates the relationship between social media and lifestyle trends on saving habits. These findings emphasize the importance of strengthening self control and the ability to manage financial priorities amid the rapid flow of information and trends on social media, so that young people can develop healthy and responsible saving habits.